FASILITASI PEMBERDAYAAN MASYARAKAT MELALUI PELATIHAN PEMBUATAN SUMUR RESAPAN - Wigati, Restu; Suryani, Irma; Bethary, Rindu Twidi (Universitas Sultan Ageng Tirtayasa, 2018)
The continuous use of ground water will have an impact on the sustainability of groundwater. One way to maintain the quality and quantity of groundwater is to apply absorption wells. In addition to increasing the amount of groundwater, the amount of surface runoff that can cause flooding problems can also be reduced. By increasing the amount of water infiltrated would affect ground water level fluctuations, so as this will have an impact on dry season where water reserves are not significantly reduced. The greater the water infiltration will have an impact on the reduced surface runoff. The application of making absorption wells in the devotion to the community in Taman Sari Village was done with a single model. Through the concept of community empowerment training by making absorption wells is expected to be a change in community behavior that is increasingly concerned and responsive to the environment, especially about the problems of flooding and drought starts from the micro level.